A Logic for Easy Linking Semantics - Eckardt, Regine (Proceedings of the Amsterdam Colloquium, 2009)
Most semantic frameworks assume that the denotations of verbs expect their arguments in a certain specific order. In fixed word order languages, hence, we could say that order codes case marking. Moreover, all syntax-semantic mappings have to provide a solution for the fact that DPs can denote individual concepts of (extensional) type e as well as generalized quantifiers (⟨⟨e,t⟩,t⟩). The paper presents a new variant of type logic which offers a lean syntax-semantics interface for semantic representation in a Montagovian format. Specifically, the syntax-semantics mapping does not require obligatory quantifier raising (as Heim+Kratzer, 1998) and does not force the semanticist to make claims about a fixed underlying order of arguments of the verb. The latter feature will facilitate semantic research on free word order languages and semantic research on languages where no syntactic analysis in a Minimalist framework is as yet available.